2016
DOI: 10.1371/journal.pone.0157432
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, Genotype Distribution and Risk Factors for Cervical Human Papillomavirus Infection in the Grand Tunis Region, Tunisia

Abstract: Implementation of Human Papillomavirus (HPV) vaccination should be considered a key cervical cancer prevention strategy in Tunisia, where Pap smear screening is not efficient. This study aims to estimate the prevalence and to identify risk factors associated with HPV infection among women from Grand Tunis, Tunisia. We conducted a cross-sectional study, between December 2012 and May 2013. Eligible women for this study were those aged 18–65 years, sexually active, who sought medical attention at their primary he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
37
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(47 citation statements)
references
References 37 publications
8
37
1
Order By: Relevance
“…The prevalence of HPV infection was slightly higher in patients over 60 years old. This is in line with published data and may be the result of an age‐related natural deterioration of the immune system, which could facilitate both viral infection and reactivation in elderly individuals . We found no significant association between mHPV positivity and sex or ultraviolet exposure …”
Section: Discussionsupporting
confidence: 92%
“…The prevalence of HPV infection was slightly higher in patients over 60 years old. This is in line with published data and may be the result of an age‐related natural deterioration of the immune system, which could facilitate both viral infection and reactivation in elderly individuals . We found no significant association between mHPV positivity and sex or ultraviolet exposure …”
Section: Discussionsupporting
confidence: 92%
“…Among women aged 25‐34 years, the frequency of infection with HPV was 28.1%, which is only slightly higher than expected or known for Eastern Europe. Of note, the incidence rates gradually and steadily decreased with age and did not show two peaks of incidence, as observed at a young age and after 50 years of age in other studies …”
Section: Discussionsupporting
confidence: 66%
“…Of note, the incidence rates gradually and steadily decreased with age and did not show two peaks of incidence, as observed at a young age and after 50 years of age in other studies. 9 Previous surveys of HPV in Bulgaria were often limited to women from a certain city or area or were designed to investigate the spread of 43.2% were found to be infected, as were 36.6% of women aged 15-24 years. 12 Shikova et al 3 also surveyed HPV in different age groups in Bulgaria, but only among prostitutes, and found that cervical HPV infection was most frequent in women aged 28 years.…”
Section: According To the Ico Information Centre On Human Papillomamentioning
confidence: 99%
“…Upon comparing this prevalence with the 17 literature articles in the general population, there was a statistically significant difference between the value found in the study (54.5%) with all results (13.7%‐40.6%).…”
Section: Resultsmentioning
confidence: 54%